I will do one, then you try
x (x^2 - 3 x - 4) = 0
x (x-4)(x+1) = 0
so x = 0 , 4 , -1
Find all real zeros for each equation.
1. f(x)=x^3-3x^2-4x
2. f(x)= x^6-x^2
3. f(x)=x^3+3x^2-16x-48
4. f(x)=9x^4-37x^2+4
3 answers
1. take out common factor of x, the rest factors
2. factor out x^2, then difference of squares.
one of them goes again.
3. x^3 + 3x^2 - 16x - 48
looks like "grouping" works here
= x^2(x+3) - 16(x+3)
= (x+3)(x^2- 16) , and a difference of squares
=(x+3)(x+4)(x-4)
4. sneaky one ...
9x^4-37x^2+4
= (x^2 - 1)(x^2 - 4)
= ..... can you finish it ?
2. factor out x^2, then difference of squares.
one of them goes again.
3. x^3 + 3x^2 - 16x - 48
looks like "grouping" works here
= x^2(x+3) - 16(x+3)
= (x+3)(x^2- 16) , and a difference of squares
=(x+3)(x+4)(x-4)
4. sneaky one ...
9x^4-37x^2+4
= (x^2 - 1)(x^2 - 4)
= ..... can you finish it ?
last one should be
4. sneaky one ...
9x^4-37x^2+4
= (9x^2 - 1)(x^2 - 4)
= ..... can you finish it ?
4. sneaky one ...
9x^4-37x^2+4
= (9x^2 - 1)(x^2 - 4)
= ..... can you finish it ?